2018
DOI: 10.1002/joc.5543
|View full text |Cite
|
Sign up to set email alerts
|

Springtime extra‐tropical cyclones in Northeast Asia and their impacts on long‐term precipitation trends

Abstract: Springtime extra‐tropical cyclones (ETCs) in Northeast Asia and the associated precipitation anomalies are examined by objectively tracking ETCs from reanalysis data. The cluster analyses reveal that Northeast Asian cyclones are largely grouped into two distinct tracks, that is, north and south tracks, depending on their pathways. The south‐track ETCs typically form over southeast China and travel towards the Japanese Islands, while the north‐track ETCs are first detected around Mongolia and move southeastward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Wang et al (2009) reported that the ETC frequency and intensity were significantly decreased in the 40°-45°N latitude band during the last few decades. Chen et al (2014) and Cho et al (2018) also documented a weakening of wintertime ETCs in China and a decreasing number of springtime ETCs in southern China, respectively. In contrast, Iwao et al (2012) showed that the number of explosive cyclones has slightly increased in the east of Japan.…”
Section: Yoshida and Asuma 2004)mentioning
confidence: 91%
“…Wang et al (2009) reported that the ETC frequency and intensity were significantly decreased in the 40°-45°N latitude band during the last few decades. Chen et al (2014) and Cho et al (2018) also documented a weakening of wintertime ETCs in China and a decreasing number of springtime ETCs in southern China, respectively. In contrast, Iwao et al (2012) showed that the number of explosive cyclones has slightly increased in the east of Japan.…”
Section: Yoshida and Asuma 2004)mentioning
confidence: 91%
“…The subscripts denote 500, 700, and 850 hPa. Additionally, extratropical cyclones (ETCs) were also detected and tracked using 6-hourly 850-hPa relatively vorticity field as in Hoskins and Hodges (2002) and Cho et al (2018), which represented the changed synoptic circulation change. Briefly, the relative vorticity was first filtered at a T42 spectral resolution and the local maximum was tracked by considering its direction and speed.…”
Section: Atmospheric Circulation Modes and Indicesmentioning
confidence: 99%
“…The quasi-stationary thermal lows were then removed by considering sufficiently strong and migrating ETCs with a minimum intensity greater than 1.0 3 10 25 s 21 [or 1 cyclonic vorticity unit (CVU)], a lifetime longer than two days, and a traveled distance greater than 1000 km (Hoskins and Hodges 2002). Tropical cyclones were also excluded by discarding cyclones that originated below 258N; see Hoskins and Hodges (2002) and Cho et al (2018) for full details.…”
Section: Atmospheric Circulation Modes and Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that more than 32 ETCs pass through the Korean Peninsula in a year. They mostly initiate in the two cyclogenesis regions, i.e., one over Mongolia on the leeside of the Altai‐Sayan mountains and the other over central China on the leeside of Tibetan Plateau (Cho et al, ; Lee et al, ). Their trajectories are consistent with the East Asian storm track (Adachi & Kimura, ; Zhang et al, ).…”
Section: Methodsmentioning
confidence: 99%